Bis(diisopropylphosphinomethyl)amine nickel(II) and nickel(0) complexes: coordination chemistry, reactivity, and catalytic decarbonylative C-H arylation of benzoxazole - Kruckenberg, Achim; Wadepohl, Hubert; Gade, Lutz H. (Organometallics, 2013)
The facile one-step synthesis of five new bis(diisopropylphosphinomethyl)amine ligands RN(CH2DIP)2 (DIP = diisopropylphosphine, R = Me-, iPr-, PhCH2-, 2-ThCH2-, and 2-FuCH2−) based on the use of the air-stable phosphonium salt [DIP(CH2OH)2]Cl is presented. The phosphonium salt cleanly reacts with primary amines to afford amine-bridged bisphosphine ligands with variable backbone substitution in good yields. These DIP ligands are useful model systems for their chiral bisphospholane analogues. The coordination chemistry of neutral nickel(II) complexes [(RDIP)NiCl2], [(RDIP)Ni(CH3)2], [(iPrDIP)Ni(Cl)CH2Si(CH3)3], and [(RDIP)Ni(CH2Ph)2], as well as coordinatively unsaturated cationic nickel(II) complexes [(RDIP)Ni(THF)CH3]+BArF- and [(RDIP)NiCH2Ph]+BArF-, has been studied by spectroscopic and X-ray diffraction methods. The cationic methyl complexes reacted cleanly with 2-butyne and 1,1-dimethylallene, yielding allylic complexes [(RDIP)Ni(pmcb)]+BArF- and [(RDIP)Ni(tma)]+BArF-, respectively (pmcb: η3-1,2,3,4,4-pentamethylcyclobutenyl; tma: η3-2,3,3-trimethylallyl). Nickel(0) complexes [(BzDIP)Ni(trans-stilbene)] and [(RDIP)Ni(C2H4)] were synthesized in one step from the corresponding dichloro complexes and have been fully characterized and analyzed by X-ray diffraction methods. [(MeDIP)Ni(C2H4)] reacted with phenyl-2-thiophenecarboxylate, yielding [(MeDIP)Ni(OPh)(2-Th)] and [(MeDIP)Ni(CO)2] in a 2:1 ratio. Both complexes were also synthesized via alternative routes. The phenolato-thienyl complex represents an intermediate in the catalytic cycle of a recently reported decarbonylative arylation of azoles. Complexes [(RDIP)Ni(C2H4)] were shown to be active catalysts for this reaction.
Gesehen am 15.06.2021